Performance of the Multibeam Satellite Return Link with Correlated Rain Attenuation - Arnau, Jesus; Christopoulos, D.; Chatzinotas, S.; C. Mosquera; Ottersten, B. (IEEE Transactions on Wireless Communications, 2014)
Rain attenuation is among the major impairments for satellite systems operating in the K band and above. In this paper, we investigate the impact of spatially correlated rain attenuation on the performance of a multibeam satellite return link. For a comprehensive assessment, an analytical model for the antenna pattern that generates the beams is also proposed. We focus on the outage capacity of the link, and obtain analytical approximations at high and low SNR. The derived approximations provide insights on the effect of key system parameters – like the inter-user distance, the satellite beam radius, or the rain intensity– and simulation results show that it fits tightly to the Monte Carlo results. Additionally, the derived expressions can be easily particularized for the single-user case, providing some novel insights.
Keywords: Antennas; Approximation methods; Attenuation; Correlation; dynacs; Rain; satcom; Satellites; Signal to noise ratio

MMSE Performance Analysis of Generalized Multibeam Satellite Channels - Christopoulos, D.; J. Arnau; Chatzinotas, S.; C. Mosquera; Ottersten, B. (Communications Letters, IEEE, 2013)
Keywords: dynacs; linear minimum mean square error receivers; multibeam satellites; Multiuser detection; return link; satcom